2016
DOI: 10.1007/s40279-016-0550-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Dimensional Interacting Constraints on Physical Activity Behaviours in the Finnish Population

Abstract: Physical activity constraints in Finland 2(18) Key PointsDespite having extensive sports facilities and physical activity recommendations physical activity levels are declining in Finland.The most dramatic decrease in physical activity within the Finnish population occurs around puberty, where girls become less active than boys.One of the possible reasons for increased inactivity may be that the design of built environments does not consider psychological or social affordances for physical activity. AbstractFi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This change still allows objective measures related to proximity to facilities and access to transportation and walking paths. This is relevant because research has shown that the availability of facilities to practice sport is a constraint to participation for some adolescents [5,37,38]. Finally, one question pertaining to the task constraint of perseverance was reworded for clarity and to reflect the purpose of the study at the suggestion of two experts.…”
Section: Validity Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This change still allows objective measures related to proximity to facilities and access to transportation and walking paths. This is relevant because research has shown that the availability of facilities to practice sport is a constraint to participation for some adolescents [5,37,38]. Finally, one question pertaining to the task constraint of perseverance was reworded for clarity and to reflect the purpose of the study at the suggestion of two experts.…”
Section: Validity Measuresmentioning
confidence: 99%
“…Recent findings also suggest that analysis of constraints to sport participation at the community level is needed to inform long term planning initiatives to increase participation [4]. This is because constraints to sport participation have been shown to vary across geographical regions due to variability in provision of resources [5][6][7], and geographical variations in socioeconomic status [4,8]. As a result, it is important to examine constraints to sport participation in order to address the challenges faced among female populations and promote overall participation in sport.…”
Section: Introductionmentioning
confidence: 99%
“…In response, both governmental and nongovernmental organizations have instituted programs to promote health through sports and physical activity. In the Scandinavian countries, participation in organized sports draws up to half of the child and adolescent population aged 10‐16 years . However, lifestyle‐related challenges, such as total cigarette and snuff tobacco use, have reported to remain the same for sports club participants as for nonparticipants .…”
Section: Introductionmentioning
confidence: 99%